Usklajevanje zdravljenja z zdravili pri prehodih bolnikov med različnimi ravnmi zdravstvene oskrbe - Jančar, Petra (Farmacevtski vestnik, 2012)
Medication errors threaten the safety, effectiveness and quality of drug therapy. Poor communication at healthcare interfaces increases the risk for medication errors due to incomplete and incorrect medication histories. Medication reconciliation has long been recognized as a mean to reduce the number and severity of those medication errors. Medication reconciliation requires i) the provision of a complete and correct medication history, ii) the identification of discrepancies with the prescribed drug therapy and iii) the resolution of any unintended discrepancy with the prescribing clinician. All changes to a patient's drug therapy have to be motivated and documented to ensure their understanding by the patient and all healthcare providers involved in their drug therapy. This paper describes the core elements of medication reconciliation and provides evidence on the need for and the role of medication reconciliation in guaranteeing the safety and effectiveness of drug therapy.
Keywords: farmacevtska skrb; klinična farmacija; predpisovanje zdravil